Edukasi Tentang Transfusi Darah Pada Pertemuan Ilmiah DPC Patelki Kota Pekalongan - Subur Wibowo (Lembaga Pengembangan Kinerja Dosen, 2024)
Blood transfusion safety is a top priority in the management of transfusion services, considering the risk of pathogen transmission and adverse transfusion reactions. With advances in technology, there are significant opportunities to improve blood filtration and processing processes, which could significantly reduce these risks. This study aims to evaluate the effectiveness of new technologies in screening and processing transfusion blood in reducing pathogen contamination and improving patient safety. This research method involves a comparative analysis of historical data on the incidence of transfusion reactions and the incidence of infection transmission before and after the implementation of pathogen filtering technology and improved blood processing systems in several blood transfusion centers. The results showed that the use of the latest pathogen screening technologies, together with improved blood processing methods, contributed significantly to reducing the incidence of infection transmission and adverse transfusion reactions. Data analysis also shows an increase in patient satisfaction and confidence in the blood transfusion process. The conclusions of this study suggest that the integration of new technologies in the screening and processing of transfusion blood is an effective strategy to improve patient safety and reduce transfusion-related risks